Pemanfaatan campuran tepung bunga Marigold (Tegates sp.) dan tepung labu kuning (Cucurbita moscahata D.) pada budidaya ikan mas koki (Carassius auratus) - Soleha, Anisa R.; Lumbessy, Salnida Y.; Azhar, Fariq (e-Journal BUDIDAYA PERAIRAN, 2022)
AbstractThe purpose of this study was to analyze the effect of using marigold flour (Tegates sp.) and pumpkin flour (Cucurbita moscahata D.) as a source of carotenoids in feed to increase the color brightness of goldfish (Carassius auratus). The method used is an experimental method with a completely randomized design, consisting of four treatments and three replications. The treatment that was tested was the concentration of a mixture of marigold flower flour and pumpkin flour added to the artificial feed formulation, namely: a mixture of marigold flower flour and pumpkin flour 0% (control) (P0), 10% (P1), 20% (P2) and 30% (P3). Research parameters include color quality, carotenoid content, absolute weight growth, absolute length growth, specific growth, feed utilization efficiency (EPP), feed conversion ratio (FCR), survival rate and water quality. Data were analyzed using Anova and continued with Duncan's test. The results showed that the addition of a mixture of marigold flower flour and pumpkin in the feed could increase the brightness of the goldfish body color but did not support optimum growth. The addition of a mixture of 30% marigold flower flour and pumpkin to the feed can improve the color brightness of goldfish better with a carotenoid content of 6.02 mol/g, a Lightness (L*) value of 76.35, a Redness(a*) value of 3.61, the value of Yellowness (b*) of 24.85 and Hue of 81.70.